The Social Dynamics of Roman Imperial Imagery - Russell, Amy (University of Cambridge ESOL Examinations, 2020)
Cover -- Half-title page -- Title page -- Copyright page -- Contents -- List of Figures -- List of Contributors -- Acknowledgements -- List of Abbreviations -- 1 Introduction: Imperial Imagery and the Role of Social Dynamics -- 2 The Altars of the Lares Augusti: A View from the Streets of Augustan Iconography -- 3 Modelling the Emperor: Representations of Power, Empire, and Dynasty among Eastern Client Kings -- 4 Publica numina: Conspicuously Consuming the Imperial Image at Tomis -- 5 Roman Emperors, Conquest, and Violence: Images from the Eastern Provinces -- 6 Court Politics and Imperial Imagery in the Roman Principate -- 7 Local Aspirations and Statues of Emperors in Roman North Africa -- 8 The Altar of P. Perelius Hedulus in Carthage and the Social Aspects of Provincial Image-Making -- 9 Imagines et tituli: Epigraphic Evidence of Imperial Imagery in Meeting Places of Roman Professional corpora -- 10 The Imperial Image in Media of Mechanical Reproduction: The Tokens of Rome -- 11 When Was an Imperial Image?: Some Reflections on Roman Art and Imagery -- Index.